2022
DOI: 10.3390/nu14204299
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Intermittent Fasting Regimens and Selection of Adequate Therapy on Inflammation and Oxidative Stress in SARS-CoV-2 Infection

Abstract: The unpredictable nature of new variants of coronavirus 2 (SARS-CoV-2)—highly transmissible and some with vaccine-resistance, have led to an increased need for feasible lifestyle modifications as complementary therapies. Systemic inflammation is the common hallmark of communicable diseases like severe coronavirus disease 2019 (COVID-19) and non-communicable chronic diseases (NCDs) such as obesity, cardiovascular diseases (CVD), diabetes mellitus, and cancers, all for which mitigation of severe outcomes is of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Overweight is a biological burden for the body, consuming additional immunological, antitoxic, and trophic functions and excretions 98 . The restricted diet (ANADETO) is considered to facilitate lipid metabolism and reduce fat mass, which could lead to suppression of inflammation 64 , 99 and the enhancement of the immune response 100 , 101 , as well as the improvement of glucose/lipid metabolism and liver functions 35 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Overweight is a biological burden for the body, consuming additional immunological, antitoxic, and trophic functions and excretions 98 . The restricted diet (ANADETO) is considered to facilitate lipid metabolism and reduce fat mass, which could lead to suppression of inflammation 64 , 99 and the enhancement of the immune response 100 , 101 , as well as the improvement of glucose/lipid metabolism and liver functions 35 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Synchronization of peripheral clocks is essential for coordinated physiology. Disruptions in circadian rhythms can lead to disturbances in metabolism, resulting in various adverse consequences, from irritability and fatigue to chronic diseases like obesity, type 2 diabetes mellitus, cardiovascular diseases, and inflammation [10,12,43,[51][52][53][54][55][56][57].…”
Section: The Circadian Regulation Of Glucose Metabolismmentioning
confidence: 99%
“…Of the various types of IF approaches, time-restricted eating (TRE), i.e., the pattern of extending the daily fasting period and thereby reducing the daily eating period, has gained popularity over the last few years [14]. Findings from our past reviews [13,[15][16][17] have suggested that TRE is a viable dietary approach to improve body composition [13,15], some metabolic parameters [15], proinflammatory markers [16,17], and oxidative stress markers [16,17], which are known risk factors for several chronic diseases including diabetes, CVD, Alzheimer's disease [16], and some cancers [17]. Furthermore, promising results from short-term and relatively small clinical trials have indicated that TRE improves fat oxidation [18], insulin sensitivity, and blood pressure, even in the absence of weight loss [19].…”
Section: Introductionmentioning
confidence: 99%